Performance of waqf institutions in Malaysia: the effects of integrated reporting, waqf governance and online digital media - Amira binti Jamil
The governance and reporting system of waqf institutions in Malaysia at this time needs to be given serious attention and updated in line with technological advance and changing trends in global accounting reporting practice. Traditional waqf reporting has proven to be less effective with a variety of recurring problem, including unproductive asset management and mismanagement. In general, the lack of transparency in reporting and inefficient governance are among the leading causes of the problems experienced by waqf institution . In line with the integrated reporting framework currently practiced globally, this study examined the current reporting practices and proposed for an integrated waqf reporting model for waqf institutions based on Maqasid Al-Shariah. This re earch also identified the effect of integrated waqf reporting and governance mechanism , namely, risk management, Shariah compliance and internal audit on the performance of waqf institutions. The role of online digital media as a moderator in this relationship i also studied. Quantitative research using survey questionnaire was conducted. The survey involved 259 stakeholder of 45 waqf institutions in Malaysia. The Structural Equation Modelling (SEM) method ha been used to test the hypotheses developed based on the agency theory and the stakeholder theory. The research findings show that the significant components of waqf reporting can be categori ed into information on cash waqf, waqf property, human capital, social and environmental capital information. The main waqf governance mechanisms are risk management, internal audit and Shariah compliance. Integrated waqf reporting has the most significant impact on waqf performance, followed by utilisation of online digital media and waqf governance mechanisms. The utilisation of online digital media does not have a moderating effect on the relationship between integrated waqf reporting and waqf performance, as well as the relationship between waqf governance and waqf performance. Furthermore the institutional structure and takeholder's group have a partial moderation effect on the relationship between the utilisation of online digital media and waqf performance, whereby the impact is more pronounced on the non-SIRC (State Islamic Religious Councils) group and external stakeholders. This study produce new empirical evidence on the impact of integrated reporting, governance practices and the utilisation of online digital media on the performance of waqf institutions from the perspective of agency theory and stakeholder theory. From the practical aspect, the results can assist waqf institutions and authorities to improve the effectiveness of waqf reporting and sustainability of these institutions in the long run through several interventions and improvements in waqf accounting, governance policies and monitoring. These include increasing the level of transparency through integrated waqf reporting, improving waqf governance and the use of online digital media.